Money Cycle Sensitivity Plot of cy:{(m4 + 3* m)*10-4} - Challoumis, Constantinos (International Journal of Global Sustainable Research, 2024)
In this work, financial liquidity has a higher rate than escape savings. The rate of the velocity of financial liquidity is two magnitudes higher than the velocity of escape savings. It uses mathematical definitions by the cycle of money and shows the sensitivity plot of cy: {(m4 + 3*m)*10-4}. In this case, financial liquidity is identical to the cycle of money.